The Application of Mobile fNIRS in Marketing Research—Detecting the “First-Choice-Brand” Effect - Krampe, Caspar; Gier, Nadine Ruth; Kenning, Peter (Frontiers in Human Neuroscience, 2018)
Recent research in the field of neuro-marketing shows promise to substantially increase knowledge on marketing issues for example price-perception, advertising efficiency, branding and shopper behaviour. In regard to shopper behaviour, recently, an innovative and mobile applicable neuroimaging method has been proposed, namely functional Near-Infrared Spectroscopy (fNIRS). A neuroimaging method that presents opportunities for marketing research. However, this method is, in the research field of marketing, still in its infancy and is, consequently, lacking substantial validity. Against this background, this research work applied a convergent validity approach to challenge the validity of (mobile) fNIRS in the field of neuro-marketing and consumer neuroscience. More precisely, we aim to replicate a robust and well-investigated neural effect previously detected with fMRI - namely the ‘first-choice-brand’ effect – by using mobile fNIRS. The given research findings show that mobile fNIRS appears to be an appropriate neuroimaging method for research in the field of neuro-marketing and consumer neuroscience. Additionally, this research work presents guidelines, enabling marketing researchers to utilise mobile fNIRS in their research work.